2013
DOI: 10.1371/journal.pone.0075238
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of Ciliates at the Water-Air Interface

Abstract: The importance of water-air interfaces (WAI) on microorganism activities has been recognized by many researchers. In this paper, we report a novel phenomenon: the entrapment of ciliates Tetrahymena at the WAI. We first characterized the behavior of cells at the interface and showed that the cells' swimming velocity was considerably reduced at the WAI. To verify the possible causes of the entrapment, we investigated the effects of positive chemotaxis for oxygen, negative geotaxis and surface properties. Even th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…In terms of scattering when stable near surface swimming does not occur, the most extensive difference was in the extent of surface residence, though a reduction in the level of scattering was also observed. These observations can be concisely understood in terms of the reduced amount of shear and thus viscous torque near the free-surface boundary compared to the no-slip scenario [53].…”
Section: Discussionmentioning
confidence: 93%
“…In terms of scattering when stable near surface swimming does not occur, the most extensive difference was in the extent of surface residence, though a reduction in the level of scattering was also observed. These observations can be concisely understood in terms of the reduced amount of shear and thus viscous torque near the free-surface boundary compared to the no-slip scenario [53].…”
Section: Discussionmentioning
confidence: 93%
“…Motion of a two-dimensional (2-D) treadmilling swimmer near a plane wall was analysed theoretically, with the observation of nonlinear periodic swimming orbits (Crowdy & Or 2010;Crowdy 2011). Also, Ferracci et al (2013) observed the trapping of fresh water ciliates (Tetrahymena thermophila) near a water-air interface.…”
Section: Introductionmentioning
confidence: 99%
“…Ciliates have a large number of hair-like organelles, termed cilia, that beat around the whole body to induce thrust force. While the remarkable activity of ciliates is usually observed in bulk water ( 11 15 ), they frequently accumulate on air/fluid and solid/fluid interfaces in nature ( 16 20 ). Although these two major characteristics (i.e., sliding on surfaces and traveling rapidly in bulk water) are commonly recognized as instinctive behaviors, the mechanism of the sliding motion remains unclear.…”
mentioning
confidence: 99%
“…Puller swimmers, which are driven by anterior flagella (e.g., Chlamydomonas ), have been numerically analyzed to determine their attractive motions toward a wall. Finally, the neutral swimmer is used as a model for ciliates that represent a uniform driving force covering the swimmer surface, assuming that cilia are beating all over the cell surface, as in Volvox ( 32 ) and Tetrahymena ( 33 ). The trajectories of neutral swimmers near a wall have been analytically and numerically reported.…”
mentioning
confidence: 99%